Adaptive space debris capture approach based on origami principle. (7th November 2019) - Sun, Chong; Wan, Wenya; Deng, Lisheng
Space debris capture is the base of the on-orbit servicing and space debris removal. Due to the lack of fixed grasping points and the uncertainty of motion parameters, the traditional spacecraft manipulator approach cannot be applied in the space debris capture. In this article, a novel adaptive capture approach based on origami principle is developed. Main advantages of the proposed method are as follows: (1) it can capture target without fixed points. Through multimodule unfolding, the capture mechanism can form a suitable configuration for the space debris, restrict its motion, and capture it. (2) As the caging configuration of the capture device can be changed through different module unfolding, it can satisfy different size of the space target. (3) It can save the launch space of the capture mechanism. The multimodule capture mechanism has small volume after folding, which can greatly save the storage space in launch stage. The structure of the capture mechanism based on origami principle is developed, and the grasping configuration design is proposed for different size of the space debris target. In addition, considering the disturbance in process of capture is nonlinear and is hard to obtain accurately, a novel extended state observer-based sliding control is developed for the capture process control. The simulation results demonstrate the efficiency of the control algorithm.